Development Workshop Leadership Clinical in Increase Competence Culture Nurse For Lowering Anxiety Levels Patients at Nurul Hasanah Hospital, Kutacane - Yusnaini Yusnaini; Arif Irpan Tanjung; Nandara Priyanti Elna (Abdimas Paspama, 2024)
Holistic nursing care requires nurses to possess cultural competence in order to provide effective and responsive care that respects patients' cultural values. Low cultural sensitivity in nursing practice can increase patient anxiety and decrease the quality of care. Clinical leadership from head nurses plays a vital role in fostering culturally sensitive nursing practices. This community service activity aims to enhance nurses' cultural competence and clinical leadership through an interactive workshop for head nurses and staff nurses at Nurul Hasanah Hospital, Kutacane . The workshop was conducted offline from August 18 to September 26, 2024, using participatory, case-based, and reflective learning approaches. Activities included the development of training modules, pre-tests, workshop implementation, post-tests, and post-training monitoring. Training materials covered clinical leadership concepts, cross-cultural communication, strategies to reduce patient anxiety, and the application of local cultural values in nursing care. Evaluation was conducted through knowledge tests and observation of follow-up action plan implementation. A total of 25 participants attended, with a 92% attendance rate. The evaluation showed an increase in the average score from 58.6 (pre-test) to 82.1 (post-test), and 76% of participants successfully implemented their follow-up plans, with several best practices documented. This activity proved effective in strengthening clinical leadership and cultural competence among nurses, contributing to reducing patient anxiety. Hospitals are encouraged to integrate cultural competency training into routine programs and ensure continuous monitoring to support implementation in care settings.